Opioid Consumption After Arthroscopic Meniscal Procedures and Anterior Cruciate Ligament Reconstruction. Issue 4 (24th April 2020) - Lovecchio, Francis; Premkumar, Ajay; Uppstrom, Tyler; Stepan, Jeffrey; Ammerman, Brittany; McCarthy, Moira; Stein, Beth Shubin; Pearle, Andrew; Taylor, Samuel; Kumar, Kanuypria; Albert, Todd; Hannafin, Jo
Background: Procedure-specific opioid-prescribing guidelines have the potential to decrease the number of unused pills in the home without compromising patient satisfaction. However, there is a paucity of data on the minimum necessary quantity to prescribe for outpatient orthopaedic surgeries. Purpose: To prospectively record daily opioid use and pain levels after arthroscopic meniscal procedures and anterior cruciate ligament reconstruction (ACLR) at a single institution. Study Design: Case series; Level of evidence, 4. Methods: A total of 95 adult patients who underwent primary arthroscopic knee surgery (meniscectomy, repair, or ACLR) were enrolled. Patients with a history of opioid dependence were ineligible. Daily opioid consumption and Numeric Rating Scale pain scores were collected through an automated text-messaging platform starting on postoperative day 1 (POD1). At 6 weeks or at patient-reported cessation of opioid use, final survey questions were asked. Patients who failed to complete data collection were excluded. Opioid use was converted into "pills" (oxycodone 5-mg equivalents) to facilitate comparisons and clinical applications. Factors associated with high and low opioid use were compared. Results: Of the 95 patients enrolled, 71 (74.7%) were included in the final analysis. Of these, 40 (56.3%) underwent meniscal surgery and 31 (43.7%) underwent ACLR. After outpatient arthroscopic meniscectomy or repair, the total median postdischarge opioid use was 0.3 pills (oxycodone 5-mg equivalents), with 75% of patients consuming 3.3 or fewer pills (range, 0-19 pills). For ACLR, the median postdischarge consumption was 7 pills (75th percentile, 23.3 pills; range, 0-41 pills). Almost one-third of patients (32.3%) took no opioids after surgery (3 ACLR, 20 meniscus). All meniscus patients and 71% of ACLR patients ceased opioid consumption by postoperative day 7. Conclusion: Opioids may not be necessary in all patients, particularly after meniscal surgery and in comparison with ACLR. For patients requesting opioids for pain relief, reasonable prescription quantities are 5 oxycodone 5-mg pills after arthroscopic meniscal procedures and 20 5-mg pills after ACLR. Slowing the current opioid epidemic and preventing future crises is dependent on refining prescribing habits. Clinicians should strongly consider patient education regarding expected pain as well as pain management strategies.